An interface buffer layer for lithium phosphorus sulfur chlorine oxygen solid-state electrolyte and lithium anode and an in-situ construction method thereof
By constructing a lithium oxide and lithium sulfide composite interface layer at the interface between the lithium phosphorus sulfur chlorine oxygen solid electrolyte and the lithium anode, the problems of lithium dendrite penetration and chemical side reactions were solved, and the synergistic effect of high modulus buffer and ion channel was achieved, thereby improving the stability and safety of the battery.
Patent Information
- Application Number
- CN202610402128.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-03-30
- Publication Date
- 2026-06-09
AI Technical Summary
The poor interfacial compatibility between lithium-phosphorus-sulfur-chlorine-oxygen solid electrolytes and lithium anodes leads to severe chemical side reactions and the risk of lithium dendrite penetration, affecting battery stability and safety.
A continuous interface layer containing lithium phosphate and crystalline phase is generated by in-situ reaction of lithium oxide and lithium sulfide in a certain molar ratio. Lithium oxide provides a high-modulus substrate, while lithium sulfide ensures ion channels. The interface structure is optimized by component gradient distribution and time-varying voltage pulse triggering reaction function.
It improves the electrochemical stability and mechanical strength of lithium batteries, inhibits the growth and penetration of lithium dendrites, reduces the occurrence of chemical side reactions, and enhances ion conductivity and battery safety.
Smart Images

Figure CN122177837A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery manufacturing technology, and more specifically, to an interface buffer layer for lithium phosphorus sulfur chlorine oxygen solid electrolyte and lithium anode and its in-situ construction method. Background Technology
[0002] Lithium-phosphorus-sulfur-chlorine electrolytes are typically composed of lithium salts (such as LiCl), phosphorus-sulfur compounds (such as P2S5), and doping elements, forming a glassy or crystalline structure. They are sulfide solid electrolytes and are core materials for all-solid-state lithium batteries, possessing high ionic conductivity and good mechanical ductility.
[0003] As one of the most studied sulfide electrolytes in recent years, lithium phosphorus sulfide chloride (LPSC) boasts high ionic conductivity and relatively low cost. However, its poor stability and incompatible positive and negative electrode materials limit its practical application. Composite solid-state electrolytes, on the other hand, exhibit excellent electrochemical and mechanical properties. To improve performance, researchers often prepare composite solid-state electrolytes through polymer modification (such as PEO and PMMA) to improve interfacial contact and electrochemical stability, aiming to enhance the interfacial compatibility and electrochemical stability of LPSCs. Despite these challenges, LPSCs remain a popular research direction in all-solid-state batteries due to their high ionic conductivity and low cost.
[0004] When sulfides (such as P2S5) in LPSClO electrolyte come into contact with lithium metal, they spontaneously react to form a high-resistivity interface layer (such as Li2S, Li3P), which hinders ion transport and causes serious chemical side reactions. In addition, the Young's modulus of sulfide electrolytes is insufficient to suppress lithium dendrite growth, and the critical current density is low, which can easily cause battery short circuits and poses a risk of lithium dendrite penetration. Summary of the Invention
[0005] Based on this, in order to solve the problems existing in the LPSClO electrolyte of the prior art, the present invention provides an interface buffer layer for lithium phosphorus sulfur chlorine oxygen solid electrolyte and lithium anode and its in-situ construction method, the specific technical solution of which is as follows:
[0006] An interfacial buffer layer for use between lithium phosphorus sulfur chlorine oxygen solid electrolyte and lithium anode is composed of lithium oxide and lithium sulfide in a molar ratio of 1:0.2-1:2. In this process, a mixture of lithium oxide and lithium sulfide powder is sprayed onto the surface of the lithium anode. During the first charge of the battery, a voltage is applied to trigger an in-situ reaction, generating lithium phosphate and... A continuous interface layer of crystalline phases.
[0007] The interface buffer layer provides a high-modulus substrate through lithium oxide and ensures ion channels through lithium sulfide, thus mitigating the defects of single materials through the use of the lithium oxide-lithium sulfide composite system; in addition, in-situ generation is introduced. / Bicrystalline phase, which can be achieved through lithium phosphate Blocking electrolyte decomposition, by A dendritic physical barrier is formed. In summary, the interface buffer layer, through in-situ electrochemical construction of a high-modulus buffer layer, solves the problems of severe chemical side reactions and the risk of lithium dendrite penetration present in existing LPSClO electrolytes.
[0008] Preferably, the composition of the interface buffer layer exhibits a non-linear gradient distribution with increasing thickness; The ratio of lithium oxide to lithium sulfide is set according to the material composition gradient distribution function, which is constructed based on the initial concentration of lithium sulfide at the lithium negative electrode interface and the distance from the lithium negative electrode interface, so as to enrich lithium oxide on the lithium side and lithium sulfide on the electrolyte side.
[0009] Preferably, applying voltage-triggered in-situ reaction during the first charging of the battery specifically includes: constructing a time-varying voltage pulse triggering reaction function based on the pulse initiation voltage, pulse peak voltage, and voltage ramp-up rate coefficient, and applying voltage-triggered in-situ reaction during the first charging of the battery based on the time-varying voltage pulse triggering reaction function.
[0010] Preferably, the preparation step of the lithium oxide and lithium sulfide mixed powder includes: Weigh lithium oxide and lithium sulfide raw materials according to the selected molar ratio, and pre-treat the weighed lithium oxide and lithium sulfide raw materials by passing them through a 200-mesh sieve in an argon-protected glove box to remove agglomerated particles. The pretreated lithium oxide and lithium sulfide raw materials were ball-milled. After ball milling, the powder was taken out from the glove box and placed in a vacuum drying oven at 60°C for 2 hours to obtain a mixed powder of lithium oxide and lithium sulfide.
[0011] Preferably, the specific steps of spraying the mixed powder of lithium oxide and lithium sulfide onto the surface of the lithium anode include: The lithium anode substrate was pretreated by wiping the surface of the lithium foil with anhydrous ethanol in an argon-protected glove box to remove oil stains, followed by plasma cleaning. Low-pressure cold spraying equipment was selected to perform cold spraying treatment of mixed lithium oxide and lithium sulfide powder in an anhydrous and oxygen-free glove box.
[0012] Preferably, the process parameters of the low-pressure cold spraying equipment include: a carrier gas pressure range of 0.8 MPa-1.2 MPa, a deposition thickness controlled between 2.0 ± 0.1 μm, and a spraying temperature between 25 ± 5 °C.
[0013] Preferably, a method for in-situ construction of an interface buffer layer for lithium phosphorus sulfur chlorine oxygen solid electrolyte and lithium anode is provided, which is used to construct the interface buffer layer in situ.
[0014] A method for in-situ construction of an interface buffer layer for lithium-phosphorus-sulfur-chlorine-oxygen solid electrolyte and lithium anode, comprising the following steps: S1, lithium oxide and lithium sulfide raw materials are ball-milled and then powder-blended; S2, cold spray deposition treatment is performed on the mixed powder; S3, voltage program activation process is performed in a segmented constant voltage manner; S4, Interface Relaxation Processing.
[0015] Preferably, the particle size of both lithium oxide and lithium sulfide after ball milling is less than 200 nm.
[0016] Preferably, the voltage program activation includes first applying a 2.5V voltage for 30 seconds, then applying a 3.2V voltage for 60 seconds, and finally applying a 3.8V voltage for 10 seconds. Attached Figure Description
[0017] The invention will be further understood from the following description taken in conjunction with the accompanying drawings. The components in the drawings are not necessarily drawn to scale, but rather the emphasis is on illustrating the principles of the embodiments. In different views, the same reference numerals designate corresponding parts.
[0018] Figure 1 This is a schematic diagram of the overall process of an in-situ construction method for an interface buffer layer in one embodiment of the present invention. Detailed Implementation
[0019] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to its embodiments. It should be understood that the specific embodiments described herein are merely illustrative of the invention and do not limit the scope of protection of the invention.
[0020] It should be noted that when an element is referred to as being "fixed to" another element, it can be directly attached to the other element or there may be an intervening element. When an element is referred to as being "connected to" another element, it can be directly connected to the other element or there may be an intervening element. The terms "vertical," "horizontal," "left," "right," and similar expressions used herein are for illustrative purposes only and do not represent the only possible implementation.
[0021] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the description of the invention is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.
[0022] In this invention, "first" and "second" do not represent a specific quantity or order, but are merely used to distinguish names.
[0023] Example 1: One embodiment of the present invention provides an interface buffer layer for lithium-phosphorus-sulfur-chlorine-oxygen solid electrolyte and lithium anode, which is composed of lithium oxide and lithium sulfide in a molar ratio of 1:0.2-1:2. Specifically, by spraying a mixed powder of lithium oxide and lithium sulfide onto the surface of the lithium anode, an in-situ reaction is triggered by applying voltage during the first charging of the battery, generating lithium phosphate and... A continuous interface layer of crystalline phases.
[0024] Specifically, the thickness of the buffer layer is 0.5-5 μm, the applied voltage range during the first charge of the battery is 2V-4V, and the ionic conductivity of the interface buffer layer is greater than 1×10⁻⁶. -4 S / cm.
[0025] Generate lithium phosphate and The continuous interface layer of the crystalline phase specifically includes the following steps: The first step is to prepare a pre-coating by cold spraying. Lithium oxide and lithium sulfide are mixed in a molar ratio of 1:0.5-1:1.5 and ball-milled to a particle size of ≤200 nm. The carrier gas pressure is 0.8–1.2 MPa for argon protection, and the substrate temperature is -30℃ to suppress lithium volatilization and sulfide decomposition. The thickness is controlled between 2.0±0.1 μm.
[0026] The second step involves the initial charging triggering a staged reaction to generate lithium phosphate and... A continuous interface layer of crystalline phases, with a time range of 0–120 s.
[0027] Phase 1: 0-60s, constant voltage of 2.8V (close to the P2S5 reduction potential of 2.7V), heating rate of 5°C / min, with lithium oxide providing the oxygen source, P2S5 dissolves from the electrolyte to participate in the reaction, generating lithium phosphate. The specific reaction pathway is as follows: To construct ion channels.
[0028] Stage 2: 60-120s, with a constant voltage of 3.5V and a heating rate of 2°C / min, activate the lithium intercalation reaction of GeS2 to generate... The specific reaction pathway is as follows: This forms a dendritic barrier layer. In lithium phosphate Epitaxial growth occurs at grain boundaries, forming an interpenetrating network.
[0029] As a preferred technical solution, the composition of the interface buffer layer exhibits a non-linear gradient distribution with thickness; wherein, the component ratio of lithium oxide to lithium sulfide is set according to a material composition gradient distribution function, which is based on the initial concentration of lithium sulfide at the lithium negative electrode interface. It is constructed by a distance z from the lithium negative electrode interface, so that the lithium side is rich in lithium oxide and the electrolyte side is rich in lithium sulfide.
[0030] For example, the material composition gradient distribution function is expressed as: The distance z from the lithium negative electrode interface ranges from [0, d], where d is the thickness of the interface buffer layer. λ represents the concentration decay coefficient, between 0.8 and 1.2 μm. k represents the secondary adjustment factor, typically between 0.05 and 0.1 μm. -2 between. This represents the compositional concentration of lithium sulfide at a distance z from the lithium anode interface, and the compositional concentration of lithium oxide at a distance z from the lithium anode interface. For 1- .
[0031] Specifically, z represents the vertical distance from a point within the buffer layer to the lithium anode interface. As the independent variable of the gradient distribution, it defines the continuous variation of component concentration along the thickness direction. When z=0, it corresponds to the lithium anode interface; when z=d, it corresponds to the solid electrolyte interface, achieving precise spatial mapping. The initial molar concentration of sulfides at the lithium anode interface is a baseline value. By setting the initial sulfide concentration near the lithium anode side, the initial energy barrier for interfacial ion conduction can be affected. The exponential decay term... It is used to dominate the rapid component transition in the near-interface region, ensuring high mechanical strength.
[0032] The concentration decay coefficient is used to control the characteristic length of the Li₂S concentration decay rate with depth. A smaller λ can lead to a sharp change in concentration, enhancing Li₂O enrichment near the lithium side and thus increasing the modulus; an excessively large λ will result in a gentle gradient, weakening the stress buffering effect. In this case, it needs to be matched with the material's thermal expansion coefficient to suppress interface cracking. The quadratic adjustment factor is a nonlinear correction coefficient, obtained through a quadratic term. The main functions of compensating for the limitations of exponential decay include: increasing the Li2S concentration in regions far from the interface to avoid a sharp drop in conductivity caused by exponential decay; balancing the gradient curvature to alleviate internal stress concentration caused by abrupt changes in composition and improve the continuity of the interface layer.
[0033] The material's composition gradient distribution function exhibits a synergistic effect. Near the lithium electrode side, a high lithium oxide concentration can increase Young's modulus, suppress lithium dendrite penetration, and enhance mechanical stability. The transition region has nonlinear gradient characteristics, which can alleviate thermo-mechanical stress mismatch and prevent interlayer peeling. Near the electrolyte side, a high lithium sulfide concentration can optimize ion transport and reduce interfacial impedance.
[0034] Thus, the Li₂O enrichment near the lithium side enhances mechanical strength, while the Li₂S enrichment near the electrolyte side strengthens ion conduction, achieving adaptive matching of interfacial stress. In summary, the material composition gradient distribution function, through the synergistic optimization of λ and k, achieves spatial decoupling between the high modulus (anti-dendrying) in the lithium-near region and the high conductivity (low polarization) in the electrolyte-near region, overcoming the performance contradictions of traditional homogeneous materials.
[0035] The interface buffer layer provides a high-modulus substrate through lithium oxide and ensures ion channels through lithium sulfide, thus mitigating the defects of single materials through the use of the lithium oxide-lithium sulfide composite system; in addition, in-situ generation is introduced. / Bicrystalline phase, which can be achieved through lithium phosphate Blocking electrolyte decomposition, by A dendritic physical barrier is formed. In summary, the interface buffer layer, through in-situ electrochemical construction of a high-modulus buffer layer, solves the problems of severe chemical side reactions and the risk of lithium dendrite penetration present in existing LPSClO electrolytes.
[0036] As a preferred technical solution, applying voltage to trigger the in-situ reaction during the first charge of the battery specifically includes: based on the pulse initiation voltage. Pulse peak voltage A time-varying voltage pulse triggering response function is constructed using the voltage ramp-up rate coefficient γ, and a voltage is applied to trigger the in-situ response during the first charge of the battery based on the time-varying voltage pulse triggering response function.
[0037] For example, the time-varying voltage pulse triggering response function is expressed as: Where t is a time variable, representing the real-time time coordinate (unit: seconds) of the pulse triggering process, accumulated from the initial moment of voltage application, through an exponential term. A gradual voltage ramp-up is achieved to avoid uncontrolled interfacial reactions caused by step voltage jumps. The pulse initiation voltage is typically between 2.0 and 2.5 V to ensure preferential formation of low-temperature phase ion channels; the pulse peak voltage is typically between 3.8 and 4.0 V to induce a high-modulus crystalline phase network. The voltage variation amplitude is controlled by the difference between the pulse peak voltage and the pulse initiation voltage to prevent electrolyte decomposition caused by overvoltage. V(t) represents the pulse voltage value at time t.
[0038] The voltage ramp-up rate coefficient reflects the system's response inertia; a smaller value indicates a smoother voltage rise, which is beneficial for ordered crystal growth. Generally, a slow voltage ramp-up synchronizes lithium-ion migration and interface reconstruction, reducing local current density and suppressing dendrite nucleation. Specifically, the voltage ramp-up rate coefficient is defaulted to 0.5 × 10⁻⁶. -3 s.
[0039] Compared to the constant voltage triggering in existing technologies, constructing a time-varying voltage pulse triggering response function can achieve the following in the triggering process: Based on the phase transition, the dendrite nucleation is suppressed by the voltage ramp rate coefficient, which can not only reduce the interface crack density, but also improve the dendrite penetration critical current and energy consumption efficiency.
[0040] This embodiment also provides an in-situ construction method for an interface buffer layer between a lithium-phosphorus-sulfur-chlorine-oxygen solid electrolyte and a lithium anode, which is used to construct the interface buffer layer in situ.
[0041] As a preferred technical solution, such as Figure 1 As shown, the in-situ construction method of the interface buffer layer for lithium phosphorus sulfur chlorine oxygen solid electrolyte and lithium anode includes the following steps: S1 involves ball milling lithium oxide and lithium sulfide raw materials and then blending them into powder.
[0042] Specifically, the particle size of both lithium oxide and lithium sulfide after ball milling is less than 200 nm. During the powder blending process, heterogeneous interface pre-contact can be formed, reducing the activation energy of the reaction.
[0043] S2, cold spray deposition treatment is performed on the mixed powder. Here, during the cold spray deposition process, parameters such as substrate temperature and carrier gas pressure can be adjusted according to the actual situation.
[0044] S3 performs voltage-programmed activation processing using a segmented constant voltage method.
[0045] The voltage-programmed activation involves applying a 2.5V voltage to the lithium negative electrode for 30 seconds, followed by a 3.2V voltage for 60 seconds, and finally a 3.8V voltage for 10 seconds, in order to suppress the lithium dendrite nucleation barrier during the gradient nucleation growth process.
[0046] S4, Interface Relaxation Processing.
[0047] Specifically, under 0.1C conditions, discharge to 2.0V and then let stand for 2 hours to improve cycle stability.
[0048] In summary, the in-situ construction method of the interface buffer layer can prevent sulfide oxidation and improve thickness accuracy through cold spray deposition; and the voltage-programmed activation treatment with constant voltage can precisely control the reaction between lithium phosphate (low-temperature phase) and... The formation time and spatial distribution of the (high temperature phase).
[0049] Example 2: One embodiment of the present invention provides an interface buffer layer for lithium-phosphorus-sulfur-chlorine-oxygen solid electrolyte and lithium anode, which is composed of lithium oxide and lithium sulfide in a molar ratio of 1:0.2-1:2. Specifically, by spraying a mixed powder of lithium oxide and lithium sulfide onto the surface of the lithium anode, an in-situ reaction is triggered by applying voltage during the first charging of the battery, generating lithium phosphate and... A continuous interface layer of crystalline phases.
[0050] Specifically, the thickness of the buffer layer is 0.5-5 μm, the applied voltage range during the first charge of the battery is 2V-4V, and the ionic conductivity of the interface buffer layer is greater than 1×10⁻⁶. -4 S / cm.
[0051] Generate lithium phosphate and The continuous interface layer of the crystalline phase specifically includes the following steps: The first step is to prepare a pre-coating by cold spraying. Lithium oxide and lithium sulfide are mixed in a molar ratio of 1:0.5-1:1.5 and ball-milled to a particle size of ≤200 nm. The carrier gas pressure is 0.8–1.2 MPa for argon protection, and the substrate temperature is -30℃ to suppress lithium volatilization and sulfide decomposition. The thickness is controlled between 2.0±0.1 μm.
[0052] The second step involves the initial charging triggering a staged reaction to generate lithium phosphate and... A continuous interface layer of crystalline phases, with a time range of 0–120 s.
[0053] Phase 1: 0-60s, constant voltage of 2.8V (close to the P2S5 reduction potential of 2.7V), heating rate of 5°C / min, with lithium oxide providing the oxygen source, P2S5 dissolves from the electrolyte to participate in the reaction, generating lithium phosphate. The specific reaction pathway is as follows: To construct ion channels.
[0054] Stage 2: 60-120s, with a constant voltage of 3.5V and a heating rate of 2°C / min, activate the lithium intercalation reaction of GeS2 to generate... The specific reaction pathway is as follows: This forms a dendritic barrier layer. In lithium phosphate Epitaxial growth occurs at grain boundaries, forming an interpenetrating network.
[0055] As a preferred technical solution, the composition of the interface buffer layer exhibits a non-linear gradient distribution with thickness; wherein, the component ratio of lithium oxide to lithium sulfide is set according to a material composition gradient distribution function, which is based on the initial concentration of lithium sulfide at the lithium negative electrode interface. It is constructed by a distance z from the lithium negative electrode interface, so that the lithium side is rich in lithium oxide and the electrolyte side is rich in lithium sulfide.
[0056] For example, the material composition gradient distribution function is expressed as: The distance z from the lithium negative electrode interface ranges from [0, d], where d is the thickness of the interface buffer layer. λ represents the concentration decay coefficient, between 0.8 and 1.2 μm. k represents the secondary adjustment factor, typically between 0.05 and 0.1 μm. -2 between. This represents the compositional concentration of lithium sulfide at a distance z from the lithium anode interface, and the compositional concentration of lithium oxide at a distance z from the lithium anode interface. For 1- .
[0057] Specifically, z represents the vertical distance from a point within the buffer layer to the lithium anode interface. As the independent variable of the gradient distribution, it defines the continuous variation of component concentration along the thickness direction. When z=0, it corresponds to the lithium anode interface; when z=d, it corresponds to the solid electrolyte interface, achieving precise spatial mapping. The initial molar concentration of sulfides at the lithium anode interface is a baseline value. By setting the initial sulfide concentration near the lithium anode side, the initial energy barrier for interfacial ion conduction can be affected. The exponential decay term... It is used to dominate the rapid component transition in the near-interface region, ensuring high mechanical strength.
[0058] The concentration decay coefficient is used to control the characteristic length of the Li₂S concentration decay rate with depth. A smaller λ can lead to a sharp change in concentration, enhancing Li₂O enrichment near the lithium side and thus increasing the modulus; an excessively large λ will result in a gentle gradient, weakening the stress buffering effect. In this case, it needs to be matched with the material's thermal expansion coefficient to suppress interface cracking. The quadratic adjustment factor is a nonlinear correction coefficient, obtained through a quadratic term. The main functions of compensating for the limitations of exponential decay include: increasing the Li2S concentration in regions far from the interface to avoid a sharp drop in conductivity caused by exponential decay; balancing the gradient curvature to alleviate internal stress concentration caused by abrupt changes in composition and improve the continuity of the interface layer.
[0059] The material's composition gradient distribution function exhibits a synergistic effect. Near the lithium electrode side, a high lithium oxide concentration can increase Young's modulus, suppress lithium dendrite penetration, and enhance mechanical stability. The transition region has nonlinear gradient characteristics, which can alleviate thermo-mechanical stress mismatch and prevent interlayer peeling. Near the electrolyte side, a high lithium sulfide concentration can optimize ion transport and reduce interfacial impedance.
[0060] Thus, the Li₂O enrichment near the lithium side enhances mechanical strength, while the Li₂S enrichment near the electrolyte side strengthens ion conduction, achieving adaptive matching of interfacial stress. In summary, the material composition gradient distribution function, through the synergistic optimization of λ and k, achieves spatial decoupling between the high modulus (anti-dendrying) in the lithium-near region and the high conductivity (low polarization) in the electrolyte-near region, overcoming the performance contradictions of traditional homogeneous materials.
[0061] The interface buffer layer provides a high-modulus substrate through lithium oxide and ensures ion channels through lithium sulfide, thus mitigating the defects of single materials through the use of the lithium oxide-lithium sulfide composite system; in addition, in-situ generation is introduced. / Bicrystalline phase, which can be achieved through lithium phosphate Blocking electrolyte decomposition, by A dendritic physical barrier is formed. In summary, the interface buffer layer, through in-situ electrochemical construction of a high-modulus buffer layer, solves the problems of severe chemical side reactions and the risk of lithium dendrite penetration present in existing LPSClO electrolytes.
[0062] As a preferred technical solution, applying voltage to trigger the in-situ reaction during the first charge of the battery specifically includes: based on the pulse initiation voltage. Pulse peak voltage A time-varying voltage pulse triggering response function is constructed using the voltage ramp-up rate coefficient γ, and a voltage is applied to trigger the in-situ response during the first charge of the battery based on the time-varying voltage pulse triggering response function.
[0063] For example, the time-varying voltage pulse triggering response function is expressed as: Where t is a time variable, representing the real-time time coordinate (unit: seconds) of the pulse triggering process, accumulated from the initial moment of voltage application, through an exponential term. A gradual voltage ramp-up is achieved to avoid uncontrolled interfacial reactions caused by step voltage jumps. The pulse initiation voltage is typically between 2.0 and 2.5 V to ensure preferential formation of low-temperature phase ion channels; the pulse peak voltage is typically between 3.8 and 4.0 V to induce a high-modulus crystalline phase network. The voltage variation amplitude is controlled by the difference between the pulse peak voltage and the pulse initiation voltage to prevent electrolyte decomposition caused by overvoltage. V(t) represents the pulse voltage value at time t.
[0064] The voltage ramp-up rate coefficient reflects the system's response inertia; a smaller value indicates a smoother voltage rise, which is beneficial for ordered crystal growth. Generally, a slow voltage ramp-up synchronizes lithium-ion migration and interface reconstruction, reducing local current density and suppressing dendrite nucleation. Specifically, the voltage ramp-up rate coefficient is defaulted to 0.5 × 10⁻⁶. -3 s.
[0065] Compared to the constant voltage triggering in existing technologies, constructing a time-varying voltage pulse triggering response function can achieve the following in the triggering process: Based on the phase transition, the dendrite nucleation is suppressed by the voltage ramp rate coefficient, which can not only reduce the interface crack density, but also improve the dendrite penetration critical current and energy consumption efficiency.
[0066] This embodiment also provides a mechanism for enhancing ionic conductivity, specifically expressed as follows: .in, Intrinsic conductivity, or the fundamental ionic conductivity of a material without interfacial phase contribution, is determined by the crystal structure of the Li₂S / Li₂O composite. Intrinsic conductivity reflects the inherent conductive capacity of the buffer layer material; an optimized value should be greater than 1 × 10⁻⁶. -4 S / cm to meet the requirements of solid-state batteries. This represents the activation energy for ion migration, which is the minimum energy required for an ion to escape the lattice bond. It is related to the defect density and bonding strength of the material; the lower the value, the smaller the energy barrier for ion transition. T represents the temperature variable.
[0067] β represents the interfacial phase contribution coefficient, which is the weighting of the lithium phosphate crystal in enhancing the overall conductivity, and its value is not less than 0.15. The interfacial phase contribution coefficient is used to quantify the contribution of the functional phase to the conduction network. Its quadratic form reflects the penetration threshold effect. When the coverage is >75%, continuous ion channels are formed, and the conductivity increases exponentially. These represent the area of the lithium phosphate crystal phase and the total effective area of the buffer layer, respectively. The coverage rate is the effective area ratio of lithium phosphate in the buffer layer, which is directly related to the degree of in-situ reaction. The coverage rate can be ensured to be no less than 75% through voltage program control.
[0068] This mechanism for enhancing ionic conductivity exhibits a dual-phase synergistic effect. and The composite is achieved through the interface phase contribution coefficient β in the function and The combined effect of volume fraction and other factors increases the ionic conductivity σ of lithium phosphate. Dendrite suppression; by adjusting the interface phase contribution coefficient, lithium phosphate crystal image area and ion migration activation energy, a decoupled design of "high ionic conductivity-high mechanical strength" can be achieved, providing a quantitative tool for solid-state battery interface engineering.
[0069] This embodiment also provides a mechanical performance optimization function, specifically expressed as follows: .in, express The volume fraction is generally required to be greater than 40% to ensure that the proportion of high modulus phase is sufficient and to improve the overall stiffness. The value represents the residual compressive strain at the interface, with a target typically set between 0.15% and 0.25%, to suppress crack propagation and improve fracture toughness through pre-compressive stress. α represents the strain hardening coefficient, an empirical value generally between 0.1 and 0.3, used to quantify the effect of residual strain on modulus gain and guide process parameters such as cold spray pressure.
[0070] In practical applications, genetic algorithms (GA) or particle swarm optimization (PSO) can be used to achieve the desired results. , As variables, minimize weight / cost while satisfying modulus constraints. In cold spraying processes, this can be controlled by carrier gas pressure. This allows for the precise introduction of residual compressive strain; in voltage-programmed activation, segmented voltages are used to regulate reaction kinetics and optimize [the process]. And crystalline phase distribution.
[0071] In summary, this mechanical property optimization function aims to address common performance conflicts in material design through multi-parameter synergistic control, such as the contradiction between modulus and conductivity, and the balance between strength and toughness. Specifically, high modulus can suppress lithium dendrite penetration, but it is usually accompanied by a decrease in ionic conductivity. The function achieves spatial decoupling through gradient design, enriching lithium oxide in the near-lithium anode region to enhance mechanical strength through high modulus, and enriching lithium sulfide in the near-electrolyte region to optimize ion transport through high conductivity; and controlling the volume fraction of the reinforcing phase (e.g., ...). The ratio of ( ) to matrix (such as lithium phosphate) is adjusted to achieve a balance between strength and crack resistance.
[0072] This embodiment also provides an in-situ construction method for an interface buffer layer between a lithium-phosphorus-sulfur-chlorine-oxygen solid electrolyte and a lithium anode, which is used to construct the interface buffer layer in situ.
[0073] As a preferred technical solution, the in-situ construction method of the interface buffer layer for lithium phosphorus sulfur chlorine oxygen solid electrolyte and lithium anode includes the following steps: S1 involves ball milling lithium oxide and lithium sulfide raw materials and then blending them into powder.
[0074] Specifically, the particle size of both lithium oxide and lithium sulfide after ball milling is less than 200 nm. During the powder blending process, heterogeneous interface pre-contact can be formed, reducing the activation energy of the reaction.
[0075] S2, cold spray deposition treatment is performed on the mixed powder. Here, during the cold spray deposition process, parameters such as substrate temperature and carrier gas pressure can be adjusted according to the actual situation.
[0076] S3 performs voltage-programmed activation processing using a segmented constant voltage method.
[0077] The voltage-programmed activation involves applying a 2.5V voltage to the lithium negative electrode for 30 seconds, followed by a 3.2V voltage for 60 seconds, and finally a 3.8V voltage for 10 seconds, in order to suppress the lithium dendrite nucleation barrier during the gradient nucleation growth process.
[0078] S4, Interface Relaxation Processing.
[0079] Specifically, under 0.1C conditions, discharge to 2.0V and then let stand for 2 hours to improve cycle stability.
[0080] In summary, the in-situ construction method of the interface buffer layer can prevent sulfide oxidation and improve thickness accuracy through cold spray deposition; and the voltage-programmed activation treatment with constant voltage can precisely control the reaction between lithium phosphate (low-temperature phase) and... The formation time and spatial distribution of the (high temperature phase).
[0081] This embodiment proposes a method for calculating the minimum stress required for a lithium dendrite penetration interface buffer layer. Function formula .in, Fracture toughness, or fracture toughness, can be understood as the ability of the buffer layer to resist crack propagation. It reflects the ultimate strength of a material against dendrite penetration and directly determines the critical stress value, with a target value of ≥1.8 MPa·m. 1 / 2 To suppress dendrite penetration. 'a' is the radius of curvature at the dendrite tip, i.e., the minimum radius of curvature at the dendrite tip. The smaller the value, the sharper the tip, the more significant the stress concentration, and the lower the critical stress. The Young's modulus of the buffer layer can be understood as the elastic modulus of the interface buffer layer. This indicates the degree of interface mismatch, which can be understood as the residual strain caused by the difference in the thermal expansion coefficients between the buffer layer and the lithium anode. represents the Young's modulus of lithium metal, which is the intrinsic elastic modulus of the lithium anode. In the function, it reflects the weakening effect of lithium metal deformation on the critical stress. h is the thickness of the buffer layer, i.e., the thickness of the interface layer. If it is too thin, the mechanical strength will be insufficient; if it is too thick, it will increase the ion transport impedance. It is generally controlled in conjunction with the Young's modulus of the buffer layer. A thinner design is allowed at high modulus. This indicates the preset reference thickness.
[0082] This formula for the critical stress function for dendrite penetration, through the coupling of fracture mechanics and interface mechanics, reveals the critical condition for dendrite penetration, its role as a core strategy for inhibiting dendrite penetration, and its correlation with material properties. , ) and microscopic parameters (a, This can provide a theoretical basis for interface design. By adjusting the corresponding parameters and combining them with gradient design, a balance between mechanical and electrical performance can be achieved.
[0083] Example 3: It should be understood that this embodiment includes at least all the technical features of the above embodiments, and further elaborates on them.
[0084] In this embodiment, the preparation steps of the lithium oxide and lithium sulfide mixed powder include: weighing lithium oxide and lithium sulfide raw materials according to the selected molar ratio, and pre-treating the weighed lithium oxide and lithium sulfide raw materials by passing them through a 200-mesh sieve in an argon-protected glove box to remove agglomerated particles; ball milling the pre-treated lithium oxide and lithium sulfide raw materials; after ball milling, taking out the powder in the glove box and placing it in a vacuum drying oven to dry it under vacuum at 60°C for 2 hours to obtain the lithium oxide and lithium sulfide mixed powder.
[0085] Since both lithium oxide and lithium sulfide are hygroscopic and easily oxidized materials, the specifications of the raw materials must be strictly controlled. Otherwise, it will lead to subsequent powder agglomeration, coating failure, and incomplete in-situ reaction. For lithium oxide and lithium sulfide raw materials, their purity should reach 99.999% or higher, removing impurities such as Na, K, and Fe to avoid side reactions caused by impurities. The initial particle size should be ≤5μm to facilitate subsequent ball milling to the nanoscale, reduce ball milling time, and store them in an anhydrous and oxygen-free environment to prevent lithium oxide from absorbing moisture and undergoing oxidation and decomposition.
[0086] A planetary ball mill can be selected as the ball mill. Specific parameters include: 1. Milling media: Zirconia balls, ball-to-material ratio 15:1.
[0087] 2. Ball milling atmosphere: high-purity argon gas, specifically, the ball milling jar is evacuated and then filled with argon gas at a pressure of 0.1 MPa to prevent powder oxidation.
[0088] 3. Rotation speed / time: 350 r / min, ball milling for 5 hours, alternating between forward and reverse rotation, changing direction every 30 minutes to prevent powder agglomeration.
[0089] 4. No grinding aids are needed, avoiding the introduction of impurities; pure physical ball milling can achieve a particle size of 200nm.
[0090] After ball milling, remove the powder from the glove box and place it in a vacuum drying oven at 60°C for 2 hours to remove trace amounts of moisture introduced during the ball milling process. After drying, seal and store.
[0091] After ball milling, the bulk density of the mixed lithium oxide and lithium sulfide powder was 0.6~0.8 g / cm³. 3 Between these parameters, the fluidity should be ≥15s / 50g to ensure uniform powder feeding during cold spraying; moisture / oxygen content: ≤20ppm to avoid pores and cracks in the film layer after spraying.
[0092] In this embodiment, the specific steps of spraying the mixed powder of lithium oxide and lithium sulfide onto the surface of the lithium anode include: The first step is to pretreat the lithium anode substrate by wiping the surface of the lithium foil with anhydrous ethanol in an argon-protected glove box to remove oil stains, followed by plasma cleaning.
[0093] Specifically, plasma cleaning is performed for 1 minute using argon plasma at a power of 100W to improve the surface roughness of the lithium foil and enhance the adhesion between the coating and the substrate. The lithium anode substrate can be industrially common 20~50μm lithium foil.
[0094] The second step involves using low-pressure cold spraying equipment to perform cold spraying of a mixture of lithium oxide and lithium sulfide powders in an anhydrous and oxygen-free glove box.
[0095] The process parameters of the low-pressure cold spraying equipment include: the carrier gas pressure range is set to 0.8MPa-1.2MPa, the deposition thickness is controlled between 2.0±0.1μm; the spraying temperature is between 25±5℃ to suppress lithium volatilization and Li2S decomposition; the spray gun moving speed is 50-100mm / s to ensure the uniformity of the coating thickness; and the distance between the spray gun and the lithium foil is set between 10~20mm to avoid powder rebound and improve deposition efficiency.
[0096] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0097] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this invention patent should be determined by the appended claims.
Claims
1. An interface buffer layer for use between a lithium-phosphorus-sulfur-chlorine-oxygen solid electrolyte and a lithium anode, characterized in that, The interface buffer layer is composed of lithium oxide and lithium sulfide in a molar ratio of 1:0.2-1:2; In this process, a mixture of lithium oxide and lithium sulfide powder is sprayed onto the surface of the lithium anode. During the first charge of the battery, a voltage is applied to trigger an in-situ reaction, generating lithium phosphate and... A continuous interface layer of crystalline phases.
2. The interface buffer layer for lithium-phosphorus-sulfur-chlorine-oxygen solid electrolyte and lithium anode as described in claim 1, characterized in that, The composition of the interface buffer layer exhibits a nonlinear gradient distribution with thickness. The ratio of lithium oxide to lithium sulfide is set according to the material composition gradient distribution function, which is constructed based on the initial concentration of lithium sulfide at the lithium negative electrode interface and the distance from the lithium negative electrode interface, so as to enrich lithium oxide on the lithium side and lithium sulfide on the electrolyte side.
3. The interface buffer layer for lithium-phosphorus-sulfur-chlorine-oxygen solid electrolyte and lithium anode as described in claim 2, characterized in that, Applying voltage-triggered in-situ response during the first charge of the battery specifically includes: constructing a time-varying voltage pulse-triggered response function based on the pulse initiation voltage, pulse peak voltage, and voltage ramp-up rate coefficient; and applying voltage-triggered in-situ response during the first charge of the battery based on the time-varying voltage pulse-triggered response function.
4. The interface buffer layer for lithium-phosphorus-sulfur-chlorine-oxygen solid electrolyte and lithium anode as described in claim 3, characterized in that, The preparation steps of the lithium oxide and lithium sulfide mixed powder include: Weigh lithium oxide and lithium sulfide raw materials according to the selected molar ratio, and pre-treat the weighed lithium oxide and lithium sulfide raw materials by passing them through a 200-mesh sieve in an argon-protected glove box to remove agglomerated particles. The pretreated lithium oxide and lithium sulfide raw materials were ball-milled. After ball milling, the powder was taken out from the glove box and placed in a vacuum drying oven at 60°C for 2 hours to obtain a mixed powder of lithium oxide and lithium sulfide.
5. The interface buffer layer for lithium-phosphorus-sulfur-chlorine-oxygen solid electrolyte and lithium anode as described in claim 4, characterized in that, The specific steps for spraying a mixed powder of lithium oxide and lithium sulfide onto the surface of a lithium anode include: The lithium anode substrate was pretreated by wiping the surface of the lithium foil with anhydrous ethanol in an argon-protected glove box to remove oil stains, followed by plasma cleaning. Low-pressure cold spraying equipment was selected to perform cold spraying treatment of mixed lithium oxide and lithium sulfide powder in an anhydrous and oxygen-free glove box.
6. The interface buffer layer for lithium-phosphorus-sulfur-chlorine-oxygen solid electrolyte and lithium anode as described in claim 5, characterized in that, The process parameters of the low-pressure cold spraying equipment include: carrier gas pressure range of 0.8MPa-1.2MPa, deposition thickness control between 2.0±0.1μm, and spraying temperature between 25±5℃.
7. A method for in-situ construction of an interface buffer layer for lithium-phosphorus-sulfur-chlorine-oxygen solid electrolyte and lithium anode, characterized in that, Used to construct an in-situ interface buffer layer as described in any one of claims 1-6.
8. The in-situ construction method of the interface buffer layer for lithium phosphorus sulfur chlorine oxygen solid electrolyte and lithium anode as described in claim 7, characterized in that, The in-situ construction method of the interface buffer layer includes the following steps: S1, lithium oxide and lithium sulfide raw materials are ball-milled and then powder-blended; S2, cold spray deposition treatment is performed on the mixed powder; S3, voltage program activation process is performed in a segmented constant voltage manner; S4, Interface Relaxation Processing.
9. The in-situ construction method of the interface buffer layer for lithium-phosphorus-sulfur-chlorine-oxygen solid electrolyte and lithium anode as described in claim 8, characterized in that, The particle size of both lithium oxide and lithium sulfide after ball milling is less than 200 nm.
10. The in-situ construction method of the interface buffer layer for lithium-phosphorus-sulfur-chlorine-oxygen solid electrolyte and lithium anode as described in claim 9, characterized in that, The voltage program activation includes first applying a 2.5V voltage for 30 seconds, then applying a 3.2V voltage for 60 seconds, and finally applying a 3.8V voltage for 10 seconds.
